Methodology of Conducting a Facilitated Discussion at the Sites of Cultural Institutions - Olga A. Staina; Polina V. Malyshenko (Управление культурой)
Topicality. At present, there is a growing interest in the search for new forms of attracting audiences to the platforms of cultural institutions. For municipal museums, the problem of attracting a new audience remains the most urgent. One of the new forms of engagement is the method of facilitated discussion. Research methods. The article discusses in detail the method of conducting a facilitated discussion. Similar cultural projects and scientific developments, articles based on this method are analyzed. Outcomes. The methodology of the discussion is presented. A facilitated discussion is a method of non-verbal communication with the viewer, which helps to create a general concept of the work in the moment with the help of an associative series and a dialogue with the presenter. The method of facilitated discussion allows the unprepared and inexperienced viewer to take an active part in the discussion of the picture. This method is characterized by the fact that the visitor to the exhibition does not need to understand the direction or history in order to be able to study the work and delve into the author's meaning. The main feature of such cultural practices as facilitated discussion is the lack of expertise and assessment of the knowledge of visitors. The visitor gets the opportunity to study and express his opinion, regardless of the level of awareness about the author, direction or historical period of the work. In the article, the method is considered on a specific example of the project "Facilitated discussion on the painting by P.S. Bortnov "The Story of a Steam Locomotive"". P.S. Bortnov is a painter from the Urals, a convicted artist of the Russian Federation. The story of his life is closely connected with Nizhny Tagil. The painting of the Ural artist is in the museum's funds. A facilitated discussion on the painting was held by the author of the article P.V. Malyshkenko within the framework of the All-Russian cultural project "Night of Museums". The algorithm for conducting the discussion is also presented in the article. Findings. The search for new forms of attracting young audiences to contemporary arts and new cultural and leisure practices remains one of the priority tasks of cultural institutions, including museums. The methods of facilitated discussion meet all modern issues of attracting new audiences. The active use and implementation of these cultural practices at the museum's sites will contribute to increasing the level of interest of the audience in museum activities. The methodology presented in the article may be of interest to students of creative universities, employees of cultural institutions, as well as teachers working in educational organizations.